2020
DOI: 10.33380/2305-2066-2020-9-2-145-150
|View full text |Cite
|
Sign up to set email alerts
|

Method of Estimating the Equivalence of Dissolution Profiles: a Modern View (Review)

Abstract: Introduction. One of the purposes of dissolution profile comparison is to establish the equivalence of dissolution profiles of the studied drug and the comparison drug.Text. According to the current regulatory documents, the main tool for quantitative confirmation of equivalence of drug release profiles is the calculation of the similarity factor (f 2). However, it does not consider the form of dissolution profiles, incomplete release of the drug substance, time correlation, and is not susceptible to the «outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study by Shohin et al 33 examined the recovery of motor strength after full-endoscopic PCFD and reported an improvement in preoperative motor weakness in 95% of patients and a full recovery of motor function in 86% of patients one year after surgery. Excellent and good outcome of minimally invasive percutaneous cervical discectomy surgeries in 82% of the cases was also reported in the literature 6 .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Shohin et al 33 examined the recovery of motor strength after full-endoscopic PCFD and reported an improvement in preoperative motor weakness in 95% of patients and a full recovery of motor function in 86% of patients one year after surgery. Excellent and good outcome of minimally invasive percutaneous cervical discectomy surgeries in 82% of the cases was also reported in the literature 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in invasive aspergillosis is high, ranging between 72 and 81% [9]. The true incidence of invasive mycoses among HIV-infected patients, however, is unknown, due to the complexity of laboratory testing and diagnosis [10]. Frequently, challenges associated with the maintenance of patients having systemic HIV take roots in the aggressive behavior of fungal lesions [11].…”
Section: Introductionmentioning
confidence: 99%